Barriers to community participation in rural tourism: a case study of the communities of Semporna, Sabah, Malaysia - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Marsland Press, 2014)
Semporna district is situated within the Tawau division, located on the southeastern coast of Sabah. The district is 1,145 square kilometers and is one of the main tourist attractions for both locals and foreign tourist. Most of Semporna’s potential for tourism lies within the natural resources of the district. In order to safeguard the sustainability of the industry, it is of unprecedented importance that there is proper use of rural tourism policies. In this argument, this paper highlights gaps and challenges in the actual scenario of the study site versus the policy texts. A full qualitative study was conducted on the heterogeneous society of Semporna and the results indicated that the local communities were not fully involved in tourism activities despite policies indicating the support of their participation. From the study several factors were identified that caused the participatory gap. This includes (i) knowledge gap, (ii) economic factors, (iii) religious factors and (iv) traditional factors. This gap indicates that the policies are under utilized and therefore there is a need for a change in management practices within the district.